Transgenic PDGF-BB sericin hydrogel potentiates bone regeneration of BMP9-stimulated mesenchymal stem cells through a crosstalk of the Smad-STAT pathways. (30th November 2022) - Zhang, Hui-Jie; Li, Fu-Shu; Wang, Feng; Wang, Han; He, Tong-Chuan; Reid, Russell R; He, Bai-Cheng; Xia, Qingyou
Abstract: Silk as a natural biomaterial is considered as a promising bone substitute in tissue regeneration. Sericin and fibroin are the main components of silk and display unique features for their programmable mechanical properties, biocompatibility, biodegradability and morphological plasticity. It has been reported that sericin recombinant growth factors (GFs) can support cell proliferation and induce stem cell differentiation through cross-talk of signaling pathways during tissue regeneration. The transgenic technology allows the productions of bioactive heterologous GFs as fusion proteins with sericin, which are then fabricated into solid matrix or hydrogel format. Herein, using an injectable hydrogel derived from transgenic platelet-derived GF (PDGF)-BB silk sericin, we demonstrated that the PDGF-BB sericin hydrogel effectively augmented osteogenesis induced by bone morphogenetic protein (BMP9)-stimulated mesenchymal stem cells (MSCs) in vivo and in vitro, while inhibiting adipogenic differentiation. Further gene expression and protein–protein interactions studies demonstrated that BMP9 and PDGF-BB synergistically induced osteogenic differentiation through the cross-talk between Smad and Stat3 pathways in MSCs. Thus, our results provide a novel strategy to encapsulate osteogenic factors and osteoblastic progenitors in transgenic sericin-based hydrogel for robust bone tissue engineering. Graphical Abstract: